2013
DOI: 10.5489/cuaj.1137
|View full text |Cite
|
Sign up to set email alerts
|

A case of indirect cauda equina syndrome from metastatic prostate cancer

Abstract: We report the case of a patient with metastatic hormone refractory prostate cancer in whom "indirect" cauda equina syndrome developed concurrent with multilevel spinal cord compression (SCC). Three months after his first positive bone scan, a 65-yearold otherwise healthy man presented with severe back pain, bilateral lower extremity paresthesias, leg weakness and urinary retention. Magnetic resonance imaging (MRI) showed a dural-based mass causing SCC at the T9, T10 and T11 vertebrae, with a normal cauda equin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…17 We theorize that cancer cells can subsequently seed within CSF, providing an alternate explanation for CNS metastases. Lefresne et al 38 reported a case of dura-based metastases at the T-4 and L4-5 levels with foraminal extension. Although the L4-5 metastasis was discovered later, we wonder if this case could be explained by perineural spread and subsequent intradural seeding, only with the L4-5 tumor lesion being somewhat salvaged and delayed by previous radiotherapy.…”
Section: Perineural Spread Beyond the Lumbosacral Plexusmentioning
confidence: 99%
“…17 We theorize that cancer cells can subsequently seed within CSF, providing an alternate explanation for CNS metastases. Lefresne et al 38 reported a case of dura-based metastases at the T-4 and L4-5 levels with foraminal extension. Although the L4-5 metastasis was discovered later, we wonder if this case could be explained by perineural spread and subsequent intradural seeding, only with the L4-5 tumor lesion being somewhat salvaged and delayed by previous radiotherapy.…”
Section: Perineural Spread Beyond the Lumbosacral Plexusmentioning
confidence: 99%
“…It had to be suitable for completion in a 6-week period, incorporate a literature review, and preferably be suitable for publication. 4 , 5 …”
Section: Ipe Program Descriptionmentioning
confidence: 99%
“…It was hypothesized to result in cauda equina flattening in a patient who had metastatic spinal lesions well above the cauda equina. 2 In a case series, 5 patients with ankylosing spondylitis who developed chronic arachnoiditis and dural fibrosis resulting in dural sac dilations had significant improvement of their pain, urinary function, and sensation after lumboperitoneal shunts. 3 Our patient experienced severe back pain presumably due in part to elevated spinal CSF pressure.…”
Section: Discussionmentioning
confidence: 99%